Human mucosal Vα7.2+CD161hi T cell distribution at physiologic state and in Helicobacter pylori infection. Issue 4 (15th June 2022) - Boonpattanaporn, Norasate; Kongkaew, Thidarat; Sengprasert, Panjana; Souter, Michael N.T.; Lakananurak, Narisorn; Rerknimitr, Rungsun; Corbett, Alexandra J.; Reantragoon, Rangsima
Abstract: Mucosal‐associated invariant T (MAIT) cells are innate‐like, unconventional T cells that are present in peripheral blood and mucosal surfaces. A clear understanding of how MAIT cells in the mucosae function and their role in host immunity is still lacking. Therefore, our aim was to investigate MAIT cell distribution and their characteristics in the gastrointestinal (GI) mucosal tissue based on Vα7.2 + CD161 hi identification. We showed that Vα7.2 + CD161 hi T cells are present in both intraepithelial layer and lamina propriae of the GI mucosa, but have different abundance at each GI site. Vα7.2 + CD161 hi T cells were most abundant in the duodenum, but had the lowest reactivity to MR1‐5‐OP‐RU tetramers when compared with Vα7.2 + CD161 hi T cells at other GI tissue sites. Striking discrepancies between MR1‐5‐OP‐RU tetramer reactive cells and Vα7.2 + CD161 hi T cells were observed along each GI tissue sites. Vα7.2 + CD161 hi TCR repertoire was most diverse in the ileum. Similar dominant profiles of TRBV usage were observed among peripheral blood, duodenum, ileum, and colon. Some TRBV chains were detected at certain intestinal sites and not elsewhere. The frequency of peripheral blood Vα7.2 + CD161 hi T cells correlated with mucosal Vα7.2 + CD161 hi T cells in lamina propriae ileum and lamina propriae colon. The frequency of peripheral blood Vα7.2 + CD161 hi T cells in Helicobacter pylori ‐infected individuals was significantly lower than uninfected individuals, but this was not observed with gastric Vα7.2 + CD161 hi T cells. This study illustrates the biology of Vα7.2 + CD161 hi T cells in the GI mucosa and provides a basis for understanding MAIT cells in the mucosa and MAIT‐related GI diseases. Graphical Abstract: Study of human Vα7.2+CD161hi T cell distribution in peripheral blood and different sites of gastrointestinal tract, its TCR characteristics and response to Helicobacter pylori infection